Increased linear bone growth by GH in the absence of SOCS2 is independent of IGF‐1 - Dobie, Ross (J Cell Physiol, 2015)
Growth hormone (GH) signaling is essential for postnatal linear bone growth, but the relative importance of GHs actions on the liver and/or growth plate cartilage remains unclear. The importance of liver derived insulin like‐growth factor‐1 (IGF‐1) for endochondral growth has recently been challenged. Here, we investigate linear growth in Suppressor of Cytokine Signaling‐2 (SOCS2) knockout mice, which have enhanced growth despite normal systemic GH/IGF‐1 levels. Wild‐type embryonic ex vivo metatarsals failed to exhibit increased linear growth in response to GH, but displayed increased Socs2 transcript levels (P < 0.01). In the absence of SOCS2, GH treatment enhanced metatarsal linear growth over a 12 day period. Despite this increase, IGF‐1 transcript and protein levels were not increased in response to GH. In accordance with these data, IGF‐1 levels were unchanged in GH‐challenged postnatal Socs2(‐/‐) conditioned medium despite metatarsals showing enhanced linear growth. Growth‐plate Igf1 mRNA levels were not elevated in juvenile Socs2(‐/‐) mice. GH did however elevate IGF‐binding protein 3 levels in conditioned medium from GH challenged metatarsals and this was more apparent in Socs2(‐/‐) metatarsals. GH did not enhance the growth of Socs2(‐/‐) metatarsals when the IGF receptor was inhibited, suggesting that IGF receptor mediated mechanisms are required. IGF‐2 may be responsible as IGF‐2 promoted metatarsal growth and Igf2 expression was elevated in Socs2(‐/‐) (but not WT) metatarsals in response to GH. These studies emphasise the critical importance of SOCS2 in regulating GHs ability to promote bone growth. Also, GH appears to act directly on the metatarsals of Socs2(‐/‐) mice, promoting growth via a mechanism that is independent of IGF‐1. J. Cell. Physiol. 9999: 2796–2806, 2015. © 2015 Wiley Periodicals, Inc.